Hematological and biochemical profile of person with macrocytic anemia in a tertiary health care centre of Nepal (Journal of Pathology of Nepal, 2020)
Background: Anemia is a nutritional problem worldwide with an increased risk of morbidity and mortality in all age groups. Macrocytic anemia often originates from abnormalities that impair the erythroid precursor maturation in the bone marrow. Since the clinical manifestations of different types of anemias are similar, hematological parameters including hemoglobin, Red blood cell indices, and Peripheral Blood Smear examination are useful in the diagnosis of anemia.Materials and Methods: This was a cross-sectional study done in the Department of Pathology at Nepal Medical College Teaching hospital. A total of 42 patients between 14 to 62 years with low Hb concentration according to the World Health Organization criteria for anemia were selected and a mean cell volume > 100 fL was taken for study. Peripheral blood smear examination, Red blood cell indices, Vitamin B12, and Folic acid level were evaluated.Results: There were 42 patients with macrocytic anemia enrolled in the study with a mean age of 31.85±12.49 years and with female preponderance. Hemoglobin level was slightly low in males compared to females. Red blood cell indices were slightly higher in males. The difference of serum Vit B12 and Folic acid in male and female was found to be significant.Conclusions: It was concluded that for the diagnosis of a specific type of anemia, hemoglobin, Red blood cell indices, reticulocytes percent, and PBS examination were important parameters. Serum Folic acid and Vitamin B12 level estimation along with other hematological parameters are important for the diagnosis of macrocytic anemia and its correlation